Book Review. Social Statistics and Ethnic Diversity: Cross-National Perspectives in Classifications and Identity Politics - Mister Gidion Maru (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
Being published as one of the book series concentrating upon the issues related to the different aspects of international migration, this edited book is published in 2015 entitled Social Statistics and Ethnic Diversity:Cross-National Perspectives in Classifications and Identity Politics. This book, edited by Patrick Simon, Victor Piche and Amelia A Gagnon, presents empirical and theoretical researches on ethnic and racial classifications in official statistics which are viewed as the reflection of the representations of population and an interpretation of social dynamics through different lenses. As results of the works of the specialists of the field, this book responds toward the resurgence of the ethnic questions in the area of statistics as portrayed in effort of the increasing number of the countries in the world that regularly launchdata concerning with ethnicity or race of their population.